(untitled) (Iter, 2022)
In this detailed and highly documented essay Bartolucci shows how important Italian influence was for Andrés Belli in its most deverse aspects. The chapter ofunpublished workf which has beenfavored here, pours over linguistic influence, being language one o f Bello’s favorite topics and for which he had a special sensitivity. The richness ofthe body o f notes shows how eagerly and accurately the author worked on the enormous amount ofnews relevant to the plot.